Lower Urinary Tract Symptoms (LUTS) among women attending gynaecology clinic and its effect on their social life - Nusee, Zalina; Busu Rerah, Ruqaiyah; MP, Htyke; Abdulwahab, Dalia F; Ramli, Roszaman; Awang, Mokhtar (Faculty of Medicine, International Islamic University Malaysia, 2016)
Objective: Lower Urinary Tract Symptoms (LUTS) is a highly prevalent disease which varies by geography and culture. It influences the quality of life and has social implication. The objectives of this study are to estimate the prevalence of LUTS among women attending our gynaecology clinic, the associated risk factors and their quality of life. Method: This is a cross sectional study on women attending gynaecology clinic in a tertiary centre. Participants were given 3 sets of validated self-answered questionnaire, UDI-6, IIQ-7 and OAB V8. Results: the prevalence of luts is 50.6% which is common among Malay women. Forty nine percent is due to stress urinary incontinence (SUI). The risk of LUTS is significantly associated with obesity (AOR = 12.14 95% CI = 1.21 to 121.99, p – value = 0.034), higher parity (AOR = 1.68 95% CI = 1.26 to 2.24, p – value = <0.001) and previous pelvic surgery (AOR = 5.38 95% CI = 1.41 to 20.62, p – value = 0.014). LUTS does not really affect our patient’s quality of life (QOL) except for travelling (1.2%) and emotion (1.6%). Conclusion: This study shows that LUTS is highly prevalent in our local population, but it has no serious effect on QOL. Further population-based study is needed for better understanding of severity and impact on quality of life